Impact of domiciliary administration of NSAIDs on COVID-19 hospital outcomes: an unCoVer analysis - Salvador, Elena; Mazzi, Cristina; De Santis, Nicoletta; Bertoli, Giulia; Jonjić, Antonija; Coklo, Miran; Majdan, Marek; Peñalvo, José L.; Buonfrate, Dora (Frontiers in Pharmacology, 2023)
Background. Effective domiciliary treatment can be useful in the early phase of COVID-19 to limit disease progression, thus pressure on hospitals. There are discrepant data on the use of non-steroidal anti-inflammatory drugs (NSAIDs). Aim of this study is to evaluate whether the clinical outcome of patients who were hospitalized for COVID-19 is influenced by domiciliary treatment with NSAIDs. Secondary objective was to explore the association between other patient characteristics/therapies and outcome. Methods. A large dataset of COVID-19 patients was created in the context of a European Union-funded project (unCoVer). The primary outcome was explored using a study level random effects meta-analysis for binary (multivariate logistic regression models) outcomes adjusted for selected factors, including demographics and other comorbidities. Results. 218 out of 1,144 patients reported use of NSAIDs before admission. No association between NSAIDs use and clinical outcome was found (unadj. OR: 0.96, 95%CI: 0.68-1.38). The model showed an independent upward risk of death with increasing age (OR 1.06; 95% CI 1.05-1.07) and male sex (1.36; 95% CI 1.04-1.76). Conclusion. In our study, the domiciliary use of NSAIDs did not show association with clinical outcome in patients hospitalized with COVID-19. Older ages and male sex showed an increased risk of death.Coronavirus disease 2019 (COVID-19) has represented a global health, social and economic challenge, overwhelming healthcare systems in many countries and heavily burdening others. Healthcare workers have been struggling to provide care, sometimes in presence of limited bed and respirator capacity, in particular in intensive care units (1). Hence, the evaluation of treatments that, given at early stage preferably at home, could prevent the progression of the infection to severe disease, was deemed relevant (2).